Óleos essencias e fungos no manejo de mosca-das-frutas(Ceratitis capilata) (WIED, 1824) e influência na qualidade de frutos da goiabeira. - Gonzaga, Kennedy Santos (2019)
Brazil is one of the world's largest fruit producers, with a production of more than 41 million tons per year. However, several pests are responsible for causing negative impacts on Brazilian fruit crops, notably the damage caused by fruit fly Ceratitis capitata (WIED, 1824). Females lay their eggs in the fruits, which will be a food resource for the developing larvae, causing significant damage to their quality. New pest control techniques, such as the use of natural products, have been developed, mainly for their effectiveness and degradability. This work consists of two scientific articles. The first article evaluates the insecticidal action of essential oils and entomopathogenic fungi on different stages of fruit fly development, the second; verifies the repellent power of oils on the adult phase of insects and evaluates the chemical composition of guava fruits Psidium guajava L. variety "Paluma" treated with essential oils. The research was conducted at the Invertebrate Zoology Laboratory belonging to the Center of Agrarian Sciences of the Federal University of Paraíba. Citronella, Carnation and Copaíba essential oils and isolates of Metarhizium anisopliae and Beauveria bassiana were used. Topical applications of 2.0 μL of each product/concentration with micropipette aid were performed on 1st, 2nd and 3rd instar larvae and pupae. There was no significant difference between the different types of oils (citronella, clove and copaíba) on larval and pupal mortality when the larvae were treated in the 1st and 2nd instar. When treated in the 3rd instar, there was a significant effect on pupal mortality. The increase in citronella oil concentration continuously increased the repelling potential. The application of essential oils did not negatively influence fruit quality.